STUDI KARAKTERISTIK MARSHALL PADA CAMPURAN ASPAL PANAS (AC-WC) DENGAN VARIASI RENDAMAN OLI BARU KENDARAAN TRUCK TRAILER - Zia Ulfata; Idayani; Kumita (Fakultas Teknik - Universitas Al Muslim - Bireuen Aceh- Indonesia, 2025)
Road pavement plays a crucial role in ensuring the smooth flow of transportation and supporting regional economic development, particularly in response to the increasing volume and axle loads of heavy vehicles. Therefore, improving the quality and durability of pavement structures is essential to ensure their long-term performance under heavy traffic conditions. One potential approach is the development of innovative asphalt mixture materials to enhance pavement performance. This study aims to evaluate the effect of incorporating fresh heavy-duty engine oil (Meditran SC 15W-40) on the Marshall characteristics of Asphalt Concrete-Wearing Course (AC-WC) hot mix. The research was conducted experimentally at the Asphalt Pavement Laboratory, Faculty of Engineering, Universitas Almuslim. The optimum asphalt content was determined to be 5.74%, while the aggregate specimens were immersed in fresh engine oil for varying durations of 0, 10, 20, 30, and 40 minutes. The evaluated Marshall parameters included stability, flow, Marshall Quotient (MQ), bulk density, Void in the Mix (VIM), Void in Mineral Aggregate (VMA), and Void Filled with Asphalt (VFA). The experimental results demonstrated that the Marshall stability increased with longer immersion durations, reaching the highest value of 1,300 kg after 40 minutes of immersion. Furthermore, all Marshall parameters satisfied the technical specifications established by the Indonesian Ministry of Public Works (2014). These findings indicate that the application of fresh heavy-duty engine oil as an aggregate immersion medium has the potential to serve as an innovative approach for enhancing the mechanical performance of AC-WC mixtures, resulting in greater strength, improved stability, and enhanced resistance to heavy traffic loading